Selection of spontaneous genotypes with high pastoral value and for multiuse systems - Vargiu M.; Nonnoi A.; Spanu E.; Salis L. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Sardinian spontaneous pastures show a remarkable biodiversity. This botanical patrimony could be valorised in land multiuse systems, such as sward reconstitution, whose degradation is often caused by human activities. Improvement of firebreak management with sward re-establishment employing local genotypes is our contribution to the VEGETATIO project (PIC INTERREG IIIA). According to the presence or absence of livestock, genotypes should have a high or scarce growing rate. Another purpose is the rediscovery of traditional plants in order to be able to provide local populations with additional income. This paper shows the results of a two-year study. After the assessment of botanical composition, some genotypes were collected and evaluated regarding their valorisation.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)